National Agricultural Science Fund (NASF): Fostering advancement in basic and strategic research in agriculture - GERARD, MANJU; MEHROTRA, SHWETA; TANWAR, RADHIKA; KUMAR, ASHOK; PRADHAN, SHARAT KUMAR (The Indian Journal of Agricultural Sciences, 2026)
The National Agricultural Science Fund (NASF) of the Indian Council of Agricultural Research has played a crucial role in strengthening basic, strategic and translational research in agriculture and allied sectors in India. The scheme supported 282 research projects involving 282 lead centers and 531 cooperating centers across the country with a cumulative funding of ₹688.01 crores. The performance and impact of NASF, analysed using quantitative data on project submissions, approvals, institutional participation, regional distribution, gender representation and research outputs, revealed that NASF-funded projects have generated around 950 publications in peer-reviewed high-impact journals along with several patents and the development and commercialisation of innovative technologies such as diagnostics, vaccines, nano and biotechnological solutions and climate-resilient agricultural interventions. NASF has contributed significantly to advancing scientific excellence, technology development and translational research to strengthen the National Agricultural Research System (NARS). The scheme has fostered multi-institutional and interdisciplinary collaborations to address national priorities and emerging challenges in agriculture. It has substantially enhanced research infrastructure, human resource capacity and scientific collaboration across institutions, to address immediate and long-term agricultural challenges related to productivity, sustainability and climate resilience. NASF fosters high-quality, collaborative agricultural research with significant implications for food security, farmer welfare and science-based policy formulation in India.